Biotransformation of graphene oxide within lung fluids could intensify its synergistic biotoxicity effect with cadmium by inhibiting cellular efflux of cadmium. (1st August 2022) - Zhu, Jianqiang; Liu, Leyi; Ma, Juan; Fu, Qingfeng; Zheng, Zhiwen; Du, E; Xu, Yong; Zhang, Zhihong
Abstract: Graphene oxide (GO) has been widely studied and applied in numerous industrial fields and biomedical fields for its excellent physical and chemical properties. Along with the production and applications of GO persist increasing, the environmental health and safety risk (EHS) of GO has been widely studied. However, previous studies almost focused on the biotoxicity of pristine GO under a relatively high exposure dose, without considering its transformation process within environmental and biological mediums. Meanwhile, its secondary toxicity or synergistic effects have not been taken seriously. Here, two different kinds of artificial lung fluids were adopted to incubate pristine GO to mimic the biotransformation process of GO in the lung fluids. And, we explored that biotransformation within the artificial lung fluids could significantly change the physicochemical properties of GO and could enhance its biotoxicity. To reveal the synergistic effects of GO and toxic metal ions, we uncovered that GO could enhance the intracellular content of metal ions by inhibiting the efflux function of ATP binding cassette (ABC) transporters which are distributed on the cellular membrane, and artificial lung fluids incubation of GO could enhance this synergistic effect. Finally, toxic metal ions induced a series of toxic reactions through oxidative stress response and promoted cell death. Moreover, consistent with the results of in vitro experiments, the lungs of mice exposed to GOs combined with Cd exhibited significant inflammation and oxidative stress compared with Cd treatment alone, and it was more remarkable within the mice which were treated with bio-transformed GOs. In summary, this study explored the impact and mechanism of biotransformation of GO in the lung fluids on the synergistic and secondary effects between GO and metal ions. Graphical abstract: Image 1 Highlights: Biotransformation changed the properties and cytotoxicity of graphene oxide (GO). GO could inhibit cellular efflux of cadmium by interaction with ABC transporters. Biotransformation enhanced the synergistic biotoxicity effects of GO with cadmium.